Dimeria fuscescens Trin. - a Grass New to Western India - Bahadur, Kr. N.; Naithani, H. B. (Indian Forester, 1970)
Dimeria fuscescens Trio., whose home is principally in Assam, is recorded for the first time from Western India, viz. Dangs forests in Southern Gujarat. The specimen was received from Dr. S.C. Pandeya, Reader in Botany, University School of Sciences, Gujarat University, Ahmedabad. Notes on its synonomy, descriptions phenology, distribution, phytogeography and distinction from allied species, together with an illustration, are provided.